The influence of high technologies on the development of civil society - Пода, Т. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2017)
The article analyzes one of the modern tendencies of formation of civil activity under the influence of high technologies. Author tried to investigate the protest activity of citizens by using the media space. It is shown that social networks play one of the decisive roles in formation of public opinion, taking the first place among the other agents of information influence.